A high torque density vernier machine for electric vehicle (EV) application - Logasan s/o Rajnthern (Nanyang Technological University, 2023)
PMSM uses a mechanical gearbox to convert high speed to low speed and hence enhance output torque. However, mechanical gears are heavy, noisy, vibrate, and have reliability issues. To run at peak efficiency, it needs to be maintained frequently, which will cost more money. Using the magnetically geared PMVM, which operates on the same principles as mechanical gears, the study seeks to replace the PMSM that is now in use. JMAG software is used to design the 12-slots, 4-pole PMSM and 12-slots, 22-pole PMVM. According to the simulation, at a rotational speed of 1200 rpm, PMVM (356.75Nm) generates a greater torque than PMSM (126.14Nm). Unfortunately, PMVM has a poor power factor value, which lowers the machine's efficiency. In comparison to PMSM and PMVM, the proposed 12-slot, 22-pole HBPMVM with 44 magnets provides a better torque of 408.23Nm and has a slight increase in power factor but not the desired value.